Diseño de un sistema de gestión de calidad para la empresa Activasalud del Ecuador cía ltda., dedicada a ofrecer soluciones empresariales en salud, ubicada al norte de la ciudad de Quito - Cajas Casa, Sandy Nataly (2013)
The main objective of the present thesis is the design of an quality management system for Activasalud company, with this we pretend to standardize all the activities that are carried out inside the company adopting a working focus based on very defined processes, this will allow it to become a more effective and committed company with the execution of the requirements and expectatives of its clients. The main activity of Activasalud company is to offer managerial solutions in health, among the services offered is the liquidating of bills, medical audit and management bills, those services are not offered by many companies in our country, it means that Activasalud possess little competition and a big objective market as clinics and hospitals of the whole country.